Front Cover: Light‐Driven Catalyst‐Free Access to Phthalazines: Entry to Antiviral Model Drugs by Merging Domino Reactions (Eur. J. Org. Chem. 5/2023). Issue 5 (24th January 2023) - Guryev, Anton; Schuster, Florian; Herrmann, Lars; Hahn, Friedrich; Wangen, Christina; Hodek, Jan; Weber, Jan; Marschall, Manfred; Tsogoeva, Svetlana B.
Abstract : The Front Cover shows a light‐induced enolization of o ‐methyl benzophenones/Diels–Alder reaction, combined with deprotection/aromatization steps in one pot toward new antiviral phthalazines. The Temple of Jupiter in the background is a colossal Roman temple in sunny Baalbek (Lebanon), that was dedicated to Jupiter Heliopolitanus, known as a SUN God. The columns of the temple on this cover picture represent the pillars of light‐induced chemistry. Cover design and photo by S. B. Tsogoeva. More information can be found in the Research Article by S. B. Tsogoeva et al .